Case Report: Radiopharmaceutical extravasation, radiation paranoia, and chilling effect - Mace, Jason; Kiser, Jackson W. (Frontiers in Nuclear Medicine, 2024)
The Society of Nuclear Medicine and Molecular Imaging (SNMMI) has publicly commented that they do not support the reporting of large extravasations to patients or regulatory bodies. The comment cites recent published articles suggesting that extravasations are infrequent and not severe. The comment stresses the importance of ensuring patients are not apprehensive or resistant to nuclear medicine procedures because of “radiation paranoia” and a “chilling effect” that can result from misinformation. Radiation paranoia and chilling effect are not defined and there are no references to specific misinformation. Our experiences and this case suggest the comment may be incongruent with real-world clinical experiences. Our severe case at a center with a long-standing focus on reducing radiopharmaceutical extravasation suggests these events can still happen, can be significant, and should be shared with our patients. Our experiences also suggest that being transparent with patients builds trust. We are concerned that a reluctance to recognize the true frequency of extravasations and their severity may create distrust in the relationship between the nuclear medicine community and patients.